Change in Mass of Spinning Black Holes Due to Change in Angular Momentum (Bulletin of Pure and Applied Sciences – Physics, 2019)
The present paper reviews the change in mass of spinning black holes w.r.t. the  angular momentum in AGN as proposed by Mahto, D. & Kumari, A. to show  that the change in mass of spinning black holes due to change in the angular  momentum decreases with increasing their masses for both categories of spin  a*=1/2 & a*=1 in the same manner provided that the change in mass of spinning  black holes w.r.t. the angular momentum for a*=1/2 is lesser than to that of  spinning black holes of the same mass for a*=1.